A preliminary investigation towards development of Islamic mobile application - Siti Mahfuzah Sarif, Ariffin Abdul Mutalib,; Fasha Rosmani, Arifah (Opción, 2019)
The aim of the study is to investigate a preliminary analysis towards development of Islamic mobile application. A semi-structured interview and a survey have been performed for the preliminary investigation as a method. As a result, the new ways of learning have evolved from traditional method to modern method via the Internet such as YouTube and Facebook, and other multimedia presentations assuming from videos, PowerPoint presentation, and mobile application. In conclusion, it is clearly revealed that the level of awareness and knowledge about Asmaul Husna among Muslim is still scarce.